Characterization of jute and glass fiber reinforced polyester based hybrid composite In this research - Hassan, MR; Gafur, MA; Rana, AA; Qadir, MR; Masum, SM; Chowdhury, AM Sarwaruddin; Karim, MM (Bangladesh Journal of Scientific and Industrial Research, 2016)
In this research work an attempt is made to fabricate a hybrid composite material with hessian cloth (natural fiber) and glass fiber (synthet ic fiber) in polyester matrix using hand lay-up process and testing was performed by ASTM standards. Main objective of this research work is to investigate the effects of use of natural fiber in the composite material with the synthetic fiber. Experimental results revealed that hybridization of composite with natural and synthetic fibers shows promising tensile strength, flexural strength and hardness. Among the hybrid composites one with the composition of three layers of glass fibers and two layers of hessian cloth (jute fiber) showed highest ten sile strength and flexural strength which were found 104.63 MPa and 134.65 MPa respectively. Water absorption was high in composites having higher hessian cloth content than glass fiber. Composite with high glass fiber content showed high hardness which was 39.9 HV. Bangladesh J. Sci. Ind. Res. 51(2), 81-88, 2016